English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Some people say this can be accomplished by using laws of cosines. I'd like to see the answer using any means possible.

Given a triangle (abc) with all angles (ABC) acute. A line is drawn from each angle to perpendicular of the opposite side. (You end up with 6 overlapping right triangles). If the distances for the perpendicular lines from each angle to each side opposite are given, can you find the perimeter (a+b+c)?

2006-12-24 12:17:19 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

One can take advantage of the fact given x, y, z, the altitudes of the triangle, a triangle with sides 1/x, 1/y, 1/z will be proportional to the original. Let A be the original triangle, B the second, and let s be the semiperimeter of A, and t of B. Then by Heron's formula, we know:

1/2 * 1/x * H = Sqrt( t(t-1/x)(t-1/y)(t-1/z) )

where H is the altitude of B. We then also have the following ratio, through proportionality:

x / H = s / t

or (x t) / H = s

Using H from above, we have:

(x t) / (2x * Sqrt( t(t-1/x)(t-1/y)(t-1/z) )) = s

or t / Sqrt( t(t-1/x)(t-1/y)(t-1/z) ) = 2s = perimeter of A, which is the answer sought, where

t = 1/2(1/x + 1/y + 1/z), as defined above.

As a check, for an equilateral triangle, where x, y, z = 1,

t = 3/2, and thus

2s = (3/2) / (Sqrt(3/16)) = 2 Sqrt(3), which is the correct answer.

2006-12-24 14:14:24 · answer #1 · answered by Scythian1950 7 · 0 0

no cosines; like this omly; check me though!
S=sqrt{p(p-a)(p-b)(p-c)} – heron’s formula for area of triangle, where p=(a+b+c)/2; on the other hand S=a*h1/2 = b*h2/2 = c*h3/2;
Or p = S/h1+S/h2+S/h3; thus heron S^2 = S^4 (1/h1+1/h2+1/h3) (1/h1+1/h2) (1/h1+1/h3) (1/h2+1/h3), hence S^2 = 1 / {(1/h1+1/h2+1/h3) (1/h1+1/h2) (1/h1+1/h3) (1/h2+1/h3)} or S=1/sqrt(g) and a+b+c = 2S (1/h1+1/h2+1/h3) / sqrt(g) = 2 sqrt(1/h1+1/h2+1/h3) / sqrt((1/h1+1/h2) (1/h1+1/h3) (1/h2+1/h3));
xmas! once more

2006-12-24 14:24:00 · answer #2 · answered by Anonymous · 0 0

hiya! hear We no longer equals the equation to 0 in spite of the indisputable fact that it quite is in accordance to question. we would desire to continually discover the fee of x for which it quite is 0. as an occasion as u have given cos2x-sinx=0 . it quite is a situation. we would desire to continually resolve it. Its answer would be cos2x=sinx sin(ninety-2x)=sinx ninety-2x=x 3x=ninety x=30

2016-12-18 18:44:34 · answer #3 · answered by biedrzycki 3 · 0 0

fedest.com, questions and answers